2015
DOI: 10.4037/ccn2015423
|View full text |Cite
|
Sign up to set email alerts
|

Nonpharmacological Interventions to Prevent Delirium: An Evidence-Based Systematic Review

Abstract: Development of delirium in critical care patients is associated with increased length of stay, hospital costs, and mortality. Delirium occurs across all inpatient settings, although critically ill patients who require mechanical ventilation are at the highest risk. Overall, evidence to support the use of antipsychotics to either prevent or treat delirium is lacking, and these medications can have adverse effects. The pain, agitation, and delirium guidelines of the American College of Critical Care Medicine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
0
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 28 publications
6
44
0
7
Order By: Relevance
“…6 If hospital staff are able to consistently implement preventive measures on an ongoing basis, delirium incidence may decrease, resulting in improved outcomes for patients and hospitals. 17 Although some research has addressed the feasibility of having ICU nurses assess for delirium, little research has tested the feasibility of nurses consistently adhering to all components of a delirium prevention bundle (DPB). 17 The purpose of this article is to report findings from a controlled interventional cohort study that tested the effectiveness of a prescriptive, nonpharmacological, nurse-led DPB in reducing delirium incidence in critically ill patients in medical-surgical ICUs.…”
mentioning
confidence: 99%
“…6 If hospital staff are able to consistently implement preventive measures on an ongoing basis, delirium incidence may decrease, resulting in improved outcomes for patients and hospitals. 17 Although some research has addressed the feasibility of having ICU nurses assess for delirium, little research has tested the feasibility of nurses consistently adhering to all components of a delirium prevention bundle (DPB). 17 The purpose of this article is to report findings from a controlled interventional cohort study that tested the effectiveness of a prescriptive, nonpharmacological, nurse-led DPB in reducing delirium incidence in critically ill patients in medical-surgical ICUs.…”
mentioning
confidence: 99%
“…16,17 Additional interprofessional strategies include educating members of the health care team about delirium in children, having multidisciplinary rounds focused specifically on delirium monitoring and treatment (eg, brain rounds, pediatric road map), order sets, protocols and practice guidelines for delirium management, and quality ICU rounds checklists to facilitate the consistent assessment and management of pain, sedation, and delirium. 1,4,23,39 Because delirium in infants and children is often unrecognized, education related to the nature and management of delirium is important for the entire pediatric health care team. 2,17,39,55,56 In a study 56 of nurses in one PICU, 11.4% incorrectly identified the Glasgow Coma Scale as the correct screening tool for delirium in children, 38.1% incorrectly indicated that benzodiazepines are helpful in treating delirium, and a majority (62%) incorrectly thought that children generally do not remember the experience of being delirious.…”
Section: Interprofessional Collaboration and Educationmentioning
confidence: 99%
“…17,22,23 Those present and caring for the child should provide frequent reorientation and calm reassurances or explanations. 16,17,21,34,39,40 Nurses and other care providers may need to repeatedly let the patient know, in an ageappropriate manner, who the staff member is, the member's role in caring for the child, what the staff member will be doing and why. 2,39 Table 7 further describes some communication strategies that can be used when engaging with a delirious child.…”
Section: Pharmacological Management Of Deliriummentioning
confidence: 99%
See 2 more Smart Citations